IPTEKS PENGHITUNGAN PAJAK PENGHASILAN TERUTANG BERDASARKAN PP NOMOR 23 TAHUN 2018 DI KELURAHAN MALENDENG KECAMATAN PAAL 2 KOTA MANADO - Budiarso, Novi Swandari; Pontoh, Winston; Wokas, Heince R.N (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
One source for implementing national development is tax revenue that reaches 75% of current state revenues, with the existence of taxes, the state can carry out development aimed at the welfare of the community itself. In fact, the voluntary awareness and concern of taxpayers is very difficult to realize if it is not forced, meaning that people are required to pay taxes in order to build a national economy. Tax collection itself still has many obstacles and challenges that come from the community itself, for example; awareness of paying taxes is still lacking in the community, the crisis of public confidence in the government and understanding of taxation itself is still very poor in terms of calculations, payments up to reporting (in this case Calculating Own Taxes - Self Assessment System), so often cause obstacles in paying taxes themselves. Malendeng, Paal 2 Subdistrict, Manado City as part of an interesting autonomous region to be observed specifically considering 1,305 taxpayers, land and building taxes, but the realization of the is only around 60.53%, namely from the small industries and household handicrafts, the medium and large industrial sectors and the service sector as well as tax revenues on the control of economic assets of the community. The problems are 1) Lack of knowledge, especially small businesses about taxes related to partner businesses and 2) Lack of ability to do tax calculation and reporting related to partner businesses, while the solutions offered are 1) Transfer of knowledge about taxes in connection with small businesses and, 2) Transfer expertise regarding tax calculation and reporting related to partner business. The method used is 2 (two) ways, namely lecture and training, lecture method with presentation techniques of material concerning taxation material, especially those involving small entrepreneurs, namely Income Tax. The training method is carried out with a simple case study of the calculation and reporting of income tax.The results achieved were an increase in the knowledge of the Malendeng villagers about income tax for micro, small and medium enterprises and an increase in the community's ability to calculate and report income taxes.Keywords : Income Tax, Small Industries, Self Assessment System